Vegetation Formation in Staphylococcus Aureus Endocarditis Inversely Correlates With RNAIII and sarA Expression in Invasive Clonal Complex 5 Isolates - Kinney, Kyle J.; Stach, Jessica M.; Kulhankova, Katarina; Brown, Matthew; Salgado-Pabón, Wilmara (Frontiers in Cellular and Infection Microbiology, 2022)
Infective endocarditis (IE) is one of the most feared and lethal diseases caused by Staphylococcus aureus. Once established, the infection is fast-progressing and tissue destructive. S. aureus of the clonal complex 5 (CC5) commonly cause IE yet are severely understudied. IE results from bacterial colonization and formation of tissue biofilms (known as vegetations) on injured or inflamed cardiac endothelium. S. aureus IE is promoted by adhesins, coagulases, and superantigens, with the exotoxins and exoenzymes likely contributing to tissue destruction and dissemination. Expression of the large repertoire of virulence factors required for IE and sequelae is controlled by complex regulatory networks. We investigated the temporal expression of the global regulators agr (RNAIII), rot, sarS, sarA, sigB, and mgrA in 8 invasive CC5 isolates and established intrinsic expression patterns associated with IE outcomes. We show that vegetation formation, as tested in the rabbit model of IE, inversely correlates with RNAIII and sarA expression during growth in Todd-Hewitt broth (TH). Large vegetations with severe sequelae arise from strains with high-level expression of colonization factors but slower transition towards expression of the exotoxins. Overall, strains proficient in vegetation formation, a hallmark of IE, exhibit lower expression of RNAIII and sarA. Simultaneous high expression of RNAIII, sarA, sigB, and mgrA is the one phenotype assessed in this study that fails to promote IE. Thus, RNAIII and sarA expression that provides for rheostat control of colonization and virulence genes, rather than an on and off switch, promote both vegetation formation and lethal sepsis.